Peran Hadits Dalam Tafsir Ilmiah: Telaah Atas Isu Sains Dalam Al-Qur'an - Ahsanul Aziz; Uswatun Hasanah (Al-Kauniyah: Jurnal Ilmu Al-Qur'an dan Tafsir, 2025)
This study explores the role and integration of Hadith in the scientific interpretation of the Qur’an (tafsir ‘ilmi), particularly concerning issues related to embryology and cosmology. As the primary source of Islamic law and guidance for humanity, the Qur’an is inseparable from the Hadith, which serves as the secondary legal foundation and an authoritative elucidation of Qur’anic meanings. This research aims to critically examine the extent to which Hadith are appropriately employed in interpreting Qur’anic verses through a scientific lens. The analysis draws upon various scientific-oriented tafsir works—from classical to contemporary—by identifying interpretations that incorporate Hadith to support scientific arguments. Utilizing content analysis within a library research framework, this study assesses the chains of transmission (sanad), textual content (matan), historical context, and the compatibility of Hadith with the verses being interpreted. The findings reveal that although Hadith play a significant role in reinforcing scientific interpretations, not all Hadith cited within such tafsir possess sufficient validity or relevance. Some narrations substantively enrich scientific interpretation, while others appear forced and misaligned with the context of the verses or the original intent of the Hadith.